Dynamic available transfer capability (ATC) evaluation by dynamic constrained optimization - Xuemin Zhang; Song, Y.H.; Qiang Lu; Shengwei Mei (IEEE transactions on power systems, 2004)
This paper proposes a method to evaluate the ATC by considering dynamic constraints. The paper adopts equilibrium equations to describe steady-state constraints of pre and postdisturbance. Dot product is used as a criterion for rotor angle stability. An algorithm based on control variable parameterization (CVP) is implemented to solve the formulated dynamic-constrained optimization (DCO) problem. A nine-bus three-machine system is used to illustrate the proposed model and algorithm.